Disability after stroke: a systematic review - Julia Fabres do Carmo; Renato Lirio Morelato; Hudson Pereira Pinto; Elizabete Regina Araujo de Oliveira
Introduction Stroke is the most common cause of disability in Western countries, yet there is no consensus in the literature on how to measure and describe disability from stroke. Objective To conduct a systematic literature review on disability in stroke survivors. Method Observational studies published in the PubMed, LILACS and SciELO online databases were selected, to evaluate disability in adults and in the elderly after stroke in the period 2002-2012. The Downs and Black checklist for non-randomized studies was used to assess the quality of the articles. Results 212 articles were found from which 16 were selected to compose the study. The mean age of participants was 67 years, and disability affected 24% to 49% of the population evaluated. With regard to measurement instruments, 31% of the studies analyzed presented results of disability by means of the modified Rankin Scale; 19% by means of the World Health Organization's International Classification of Functioning, Disability and Health; 19% by means of Katz' Index of Independence in Activities of Daily Living; 12.5% by means of the London Handicap Scale; 12.5 % by means of the Barthel Index; and 6.25% by means of the Functional Independence Measure. Conclusion Literature is not uniform as regards means of measuring disability after stroke, but considering the preference of articles in assessing physical performance in activities of daily living, it can be concluded that a quarter to half of the population that survives stroke has some degree of disability.